Generation of High Peak Power Pulses With Controllable Repetition Rate in Doubly Q-Switched Laser With AOM/SnSe2 - Xia, Jingxuan; Dong, Xu; Yuan, Hanming (Frontiers in Physics, 2022)
By simultaneously employing self-made SnSe2 saturable absorber (SA) and an acous-to-optic modulator (AOM), a dual-loss-modulated Q-switched Nd:YVO4 laser with short pulse width, high peak power and adjustable pulse repetition rate is presented. The maximum pulse peak power of 37.57 KW with the minimum pulse duration of 5.52 ns were obtained under the pump power of 8 W and the pulse repetition rate of 5 kHz. The experimental results demonstrate that the dual-loss modulation technology with AOM and SnSe2 SA is a simple and efficient method to generate short pulses with high peak power and adjustable low repetition rates.